PENGUATAN TATA KELOLA KEUANGAN LINGKUNGAN MELALUI SISTEM LAPORAN KEUANGAN DIGITAL PADA KOMPLEK GRAND MUTIARA RESIDENCE - Wira Apriani (JURNAL PENGABDIAN KEPADA MASYARAKAT, 2026)
Environmental financial management is an important aspect in supporting the sustainability of operations and shared services within residential communities. However, financial records that are still managed manually often lead to problems such as disorganized data, limited transparency, and low accountability in the management of community funds. This community service activity aims to strengthen environmental financial governance through the implementation of a digital financial reporting system for the management of Grand Mutiara Residence. The implementation method includes partner needs analysis, design of a digital financial reporting system, system implementation, training and assistance for administrators, and evaluation of program implementation. The digital financial reporting system is used to record community cash inflows and outflows and to generate periodic financial reports. The results show that the implementation of a digital financial reporting system improves the orderliness of financial records, facilitates report preparation, and enhances transparency and accountability in the management of community funds. In addition, administrators demonstrated improved capability in independently managing finances using the digital system. Therefore, this community service activity makes a tangible contribution to strengthening more orderly and sustainable environmental financial governance.